A unified method to energy-to-peak filter design for networked Markov switched singular systems over a finite-time interval. Issue 17 (November 2017) - Song, Xiaona; Wang, Zhen; Shen, Hao; Li, Feng; Chen, Bo; Lu, Junwei
Abstract: For a class of networked singular Markov switched discrete-time systems, this work investigates the finite-time energy-to-peak filtering problem. The system modes information is transmitted though an unreliable communication link in the systems under consideration, where the packet dropout phenomenon, modes information available to the filter and asynchronous phenomenon between filter modes and system modes are randomly occurring with a certain probability and described by some Bernoulli distributed white sequence variables. The objective is focused on designing a unified filter, which covers mode-independent filter, asynchronous filter and mode-dependent filter, so that the estimation error system is finite-time bounded while meets a fixed energy-to-peak performance requirement in the presence of those stochastic phenomena. By employing a probability-dependent Lyapunov–Krasovskii function, some sufficient criteria are established to make sure that there is a feasible solution to the addressed problem. Moreover, with the help of a novel simple matrix decoupling approach, the filter gains are obtained. In the end, we employ a numerical example with simulation to show the serviceability of the presented method.